Association of polymorphic loci of susceptibility to diabetes mellitus type 2 in various ethnic groups of the Russian Federation - D. S. Avzaletdinova; T. V. Morugova; L. F. Sharipova; O. V. Kochetova (Сахарный диабет)
The multifactorial nature of type 2 diabetes mellitus (T2D) was confirmed by numerous researches. The first investigations devoted to molecular-genetic mechanisms of T2D were carried out on the basis of linkage disequilibrium (LD) studying and later the candidate genes of T2D have begun investigated. We have analyzed the literature data including the case-control studies in populations of Russia. There were revealed 33 genes and 65 polymorphic markers in the analyzed works. The analysis of association of T2D in the ethnic groups of Russian Federation was carried out on following genes: ABCC8, ADIPOQ, ADIPOR1, ADIPOR2, C2CD4A/C2CD4A, CDKAL1, CDKN2A/2B, CCL11, CCL20, CCL5, CYBA, FABP2, FTO, GCLC, GPX2, GSTP1, GSTT1, HHEX/IDE, IGF2BP2, IRS1, KCNJ11, KCNQ1, LPL, LRP5, MC4R, PPARG, SLC2A2, SLC30A8, SLC30A8, TCF7L2, TMEM18, WFS1, ZFAND6. The major of studies are replicative, i.e. repeating previous investigations of foreign authors, and were performed on Russian, Tatar and Yakut populations. At the same time not all the loci of genetic susceptibility have demonstrated the association with T2D in the population of Russia. In this work the systematic review of studies of molecular-genetic markers of T2D in the ethnic groups of Russian Federation was made for the first time.